Arrojando luces sobre el elefante: Caso del sistema ecoagroalimentario del trigo panadero chileno - Bonilla-Muñoz, V. H.; Marín, C. (Agro Sur, 2018)
Healthy diets: reality or dystopia? There is a solid consensus on the non-sustainability of the global eco-agri-food system1 (TEEB, 2018), given that it is responsible for 60% of biodiversity loss (Sukhdev et al., 2016), and fails to feed well 50% of humanity (FAO, 2018). This situation is exacerbated in Chile, with 65% of the population being poorly nourished (PAHOWHO, 2018). Bread is the main source of calories and proteins for all socioeconomic classes in Chile (Crovetto et al., 2014). Under this scenario, it is at least ambitious to guarantee healthy lives to achieve the ...